Transfer of Ownership Rights to Land Due to Inheritance Based on Customary Law in Semidang Alas Maras Subdistrict in terms of Civil Inheritance (Fakultas Hukum Dehasen, 2021)
The purpose of this study was to determine the transfer of ownership rights to land due to inheritance based on customary law in Semidang Alas Maras District in terms of Civil Inheritance. This study uses an empirical juridical approach. This approach aims to understand that the law is not merely a set of statutory rules that are normative in nature, but the law is understood as the behavior of people who are symptomatic in their lives, always interact and relate to social aspects, such as; economic, social and cultural aspects. 2. Transfer of land rights regarding the skills and authority to act from those who will transfer and receive the transfer of land rights. Constraints that occur in the implementation of the transfer of ownership rights to land due to inheritance are caused by the community's reluctance to certify their land because the community assumes that the services provided by the land office are very difficult and take a long time and are relatively expensive for people with low economic groups.